Evaluation of a Java microprocessor for use in future SUNSAT satellites - La Grange, Philip(Philip Lodewyk) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Ing) -- University of Stellenbosch, 2002.